2018
DOI: 10.1080/14740338.2018.1442431
|View full text |Cite
|
Sign up to set email alerts
|

The nature, magnitude, and reporting compliance of device-related events for intravenous patient-controlled analgesia in the FDA Manufacturer and User Facility Device Experience (MAUDE) database

Abstract: Patients on IV-PCA continue to experience serious complications as a result of preventable errors. Multi-modal interventions including educational training and the development and adoption of PCA devices with improved safety features are needed to improve safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Misclassification of harmful IV-PCA errors was also reported in a similar study by Lawal and colleagues. 28 Taken together, these findings indicate that harmful IV-PCA errors are common and frequently lead to adverse outcomes warranting additional care and healthcare resource utilization.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Misclassification of harmful IV-PCA errors was also reported in a similar study by Lawal and colleagues. 28 Taken together, these findings indicate that harmful IV-PCA errors are common and frequently lead to adverse outcomes warranting additional care and healthcare resource utilization.…”
Section: Discussionmentioning
confidence: 88%
“…healthcare professionals and patients). 28 , 47 Additionally, since the acquisition of MEDMARX by Quantros in 2008, there has been a systematic decline in the number of facilities reporting opioid-related medication errors to the database. This decline may have led to an underestimation of the number of errors reported.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2005 and 2009, the FDA recorded more than 710 deaths related to infusion pumps, specifically citing drug overdoses as one cause [15]. A recent review of the FDA Manufacturer and User Facility Device Experience database by Lawal et al focusing on the intravenous administration route concluded that "patients on IV-PCA continue to experience serious complications as a result of preventable errors" [16]. However, changes in the design, improved user interfaces, and tightening of regulations might have led to a decrease of incidents compared to years at the beginning of the century although an increase in reporting due to legal requirements in recent years could contradict this hypothesis.…”
Section: Technology: Safety As Itsmentioning
confidence: 99%
“…However, changes in the design, improved user interfaces, and tightening of regulations might have led to a decrease of incidents compared to years at the beginning of the century although an increase in reporting due to legal requirements in recent years could contradict this hypothesis. In the event of a device issue, the majority of patients suffer from adverse events, whereby inadequate analgesia dominates [16,17].…”
Section: Technology: Safety As Itsmentioning
confidence: 99%
“…10 Using the MAUDE database, previous research found that 92% of the 1430 reports involving patient-controlled intravenous analgesia devices were classified as device malfunctions. 11 However, that study did not analyze the number of device malfunction reports related to elastomeric pumps. Elastomeric pump malfunctions resulting in overinfusion of anesthetic have also been reported in the literature, further supporting the need to evaluate reports of device malfunctions and events, such as LAST, associated with these devices.…”
Section: Introductionmentioning
confidence: 99%